Mathematical Modeling of Helicopter Dynamics with an External Sling Load - Viktorovich Efimov, Vadim; Olegovich Chernigin, Konstantin; Ivanovich Nikolaykin, Nikolay; Vadimovich Vorob’ev, Vadim; Semenovich Kublanov, Mikhail (International Journal of Engineering and Technology, 2018)
The article shows the urgency of the development of theoretical methods for studying the dynamics of the flight of a helicopter with an external sling load aimed at ensuring the flight operation safety when transporting loads. A mathematical model of the helicopter flight dynamics with an external sling load is described. The assumptions made are indicated. The load coordinate systems are introduced and described. The systems of equations of acting forces and moments are presented, which are derived considering the accelerated movement of the load's slinging point on the helicopter with its translational and rotational motion.Â Â Â